2014
DOI: 10.1111/pme.12464
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Routes to Oral Opioid Administration in Palliative Care: A Review and Clinical Summary

Abstract: This review is not designed to be a critical appraisal of the quality of current evidence; rather, it is a summation of that evidence and of current clinical practices regarding alternate routes of opioid administration. In doing so, the overarching goal of this review is to support more informed clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 141 publications
(188 reference statements)
0
16
0
2
Order By: Relevance
“…Oral administration of drugs may be a good alternative to other routes as it is noninvasive, easy to administer and may produce less pronounced adverse effects (Kestenbaum et al, 2014). Previous studies reported administration of lipid-soluble and water-soluble opioids in horses, such as sublingual buprenorphine (Messenger et al, 2011), oral methadone (Linardi et al, 2009(Linardi et al, , 2012 and oral tramadol (Shilo et al, 2008;Cox et al, 2010;Guedes et al, 2013), but there is no information about possible antinociceptive effects using oral or buccal opioids in such species.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of drugs may be a good alternative to other routes as it is noninvasive, easy to administer and may produce less pronounced adverse effects (Kestenbaum et al, 2014). Previous studies reported administration of lipid-soluble and water-soluble opioids in horses, such as sublingual buprenorphine (Messenger et al, 2011), oral methadone (Linardi et al, 2009(Linardi et al, , 2012 and oral tramadol (Shilo et al, 2008;Cox et al, 2010;Guedes et al, 2013), but there is no information about possible antinociceptive effects using oral or buccal opioids in such species.…”
Section: Introductionmentioning
confidence: 99%
“…While important and often essential in this group of patients, opioids are also a potential cause of adverse events and should be used with caution. ( 32 ) Conversely, terminal sedation was found to be limited to a few cases. This was not surprising, as terminal sedation is a last resource strategy for management of refractory symptoms and pain.…”
Section: Discussionmentioning
confidence: 99%
“…As patients approach end of life, up to 70% of patients require a nonoral route (NPO) for opioid administration. 21 Dysphagia and mucositis can occur in head and neck, esophageal, and gastric cancers and can be a key barrier to optimal palliation of pain. Neuromuscular and sensory damage due to combined chemother-apy, radiation, and surgery can affect any stage of the swallowing mechanism.…”
Section: Opportunities For Tirfs In the Palliative Care Settingmentioning
confidence: 99%